Performance of a prototype micro wind turbine in the manmade wind field from air conditioner of buildings - K. H. Goh (QScience Connect, 2012)
Harnessing waste energy from the manmade air fields of buildings presents a new area of renewable energy to explore. Due to the unpredictability of the natural wind, this study is to evaluate the practicality for harnessing waste energy from the air conditioner exhaust units which are a more constant and predictable source available in the buildings. A prototype of the micro wind turbine has been designed to minimize the negative effect of the exhaust sources. After the micro wind turbine was manufactured, the performance of the turbine was tested in the selected air conditioner exhaust unit. Increasing the rotor solidity and decreasing the resistance of the generator contribute to improved starting torque and decreased generator break in torque respectively in the design. The power generation of the micro wind turbine increases with an increase of the rotor speed. The 24-hour operation of the prototype presents an observation for both exhaust performance and power generation prediction when the prototype is mounted on the exhaust unit.